Engaging with the politics of water governance. (11th September 2017) - Zwarteveen, Margreet; Kemerink‐Seyoum, Jeltsje S.; Kooy, Michelle; Evers, Jaap; Guerrero, Tatiana Acevedo; Batubara, Bosman; Biza, Adriano; Boakye‐Ansah, Akosua; Faber, Suzanne; Cabrera Flamini, Andres; Cuadrado‐Quesada, Gabriela; Fantini, Emanuele; et al.
Abstract : The goal of the study is to strengthen the analytical purchase of the term water governance and improve the utility of the concept for describing and analyzing actual water distribution processes. We argue this is necessary as most writing on water governance is more concerned with promoting particular politically inspired agendas of what water governance should be than with understanding what it actually is. We believe that water governance at heart is about political choices as to where water should flow; about the norms, rules and laws on which such choices should be based; about who is best able or qualified to decide about this; and about the kind of societal future such choices support. We identify distributions—of water, voice and authority, and expertise—as the empirical anchor and entry‐point of our conceptualization of water governance. This usefully allows foregrounding questions of equity in water governance discussions and provides the empirical foundation for a meaningful engagement with the politics of water governance. WIREs Water 2017, 4:e1245. doi: 10.1002/wat2.1245 This article is categorized under: Engineering Water > Planning Water Human Water > Rights to Water Human Water > Water Governance Abstract : Foregrounding questions of equity by conceptualizing water governance as distributions of water, knowledge and expertise, and voice and authority